2015
DOI: 10.1111/cup.12489
|View full text |Cite
|
Sign up to set email alerts
|

Trichoblastoma, syringocystadenoma papilliferum, desmoplastic trichilemmoma and tumor of the follicular infundibulum with signet‐ring cells, all arising in nevus sebaceus

Abstract: Herein, we describe a 63-year-old male with multiple tumors arising within a nevus sebaceus on the posterior scalp. On histopathologic examination, four distinct tumors were identified: trichoblastoma, syringocystadenoma papilliferum, desmoplastic trichilemmoma and tumor of the follicular infundibulum (TFI). Within the TFI component of the nevus sebaceus, there was intracytoplasmic accumulation of eosinophilic keratin, as shown on pancytokeratin-stained sections, imparting a signet-ring appearance to the cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
0
11
0
2
Order By: Relevance
“…7 However, sometimes DT develops from nevus sebaceous. 5,[13][14][15] DT can develop concomitantly with a variety of other adnexal tumors, such as trichoblastoma; 5 it also may occur in combination with basal cell carcinoma (BCC). 11,15,16 Histologically, a DT lesion is lobulated with a clear boundary that extends into the dermis and is continuous with the epidermis.…”
Section: Discussionmentioning
confidence: 99%
“…7 However, sometimes DT develops from nevus sebaceous. 5,[13][14][15] DT can develop concomitantly with a variety of other adnexal tumors, such as trichoblastoma; 5 it also may occur in combination with basal cell carcinoma (BCC). 11,15,16 Histologically, a DT lesion is lobulated with a clear boundary that extends into the dermis and is continuous with the epidermis.…”
Section: Discussionmentioning
confidence: 99%
“…DT is an uncommon histological subtype of trichilemmoma, and only 10 cases of DT arising within NSJ have been described [ 8 , 11 , 15 , 16 ]. Histopathologically, DT presents as a well-defined lobular tumor with typical features of trichilemmoma at the periphery and a central desmoplastic stroma.…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of TFI in 1961, there have been many accounts of associated neoplasms ( Table I ). 9 , 13 , 14 , 15 , 16 , 17 , 19 , 20 , 21 One of the first mentions of TFI-associated lesions was in 1989, by Kossard et al. 6 In studying eruptive infundibulomas, they found that the platelike epithelial architecture of TFI was seen in association with seborrheic keratoses and BCC.…”
Section: Discussionmentioning
confidence: 99%